Syncretism of Confucianism, Buddhism and Daoism in Liaozhai Zhiyi in Terms of Filial Piety - Aiqing Wang (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2021)
Liáozhāi Zhìyì is one of the representative compilations in the genre of zhìguài ‘strange writing’ during the Qing (1644-1912) era, and it conveys filial piety through narration and authorial commentary. This research scrutinizes narratives regarding the preponderant construal of filial piety, so as to explore the harmonious contemporaneous of religious thinking and behavior in Qing China. This research conducts interpretative and hermeneutic research on four narratives in Liáozhāi Zhìyì, namely, Xí Fāngpíng, Lè Zhòng, Sìshí Qiān, and Qiánbǔ Wū, and  also refers to classic treatises regarding filial piety. Given the fact that narratives in Liáozhāi Zhìyì themed by or appertaining to filial piety entail elements of three religions simultaneously. This study propounds that it illuminates amalgamation of Confucianism, Buddhism and Daoism, i.e. sānjiàohéyī, in seventeenth-century China.